Migration systems, pioneers and the role of agency - Bakewell, O; de Haas, H; Kubal, A (International Migration Institute, 2011)
The notion of a migration system is often invoked but it is rarely clearly defined or conceptualized. De Haas has recently provided a powerful critique of the current literature highlighting some important flaws that recur through it. In particular, migration systems tend to be identified as fully formed entities, and there is no theorization as to how they come into being. Moreover, there is no explanation of how they change in time, in particular how they come to decline. The inner workings – the mechanics – which drive such changes are not examined. Such critiques of migration systems relate to wider critiques of the concept of systems in the broader social science literature, where they are often presented as black boxes in which human agency is largely excluded. The challenge is how to theorize the mechanics by which the actions of people at one time contribute to the emergence of systemic linkages at a later time. This paper focuses on the genesis of migration systems and the notion of pioneer migration. It draws attention both to the role of particular individuals, the pioneers, and also the more general activity of pioneering which is undertaken by many migrants. By disentangling different aspects of agency, it is possible to develop hypotheses about how the emergence of migrations systems is related to the nature of the agency exercised by different pioneers or pioneering activities in different contexts.